Territorial division of labor in industry. The participation of female labor - Reolon, Cleverson Alexsander; Sposito, Eliseu Saverio [UNESP] (Revues Org, 2024)
In this text, we analyze the geographical aspects of women's insertion on the formal labor market in Brazil and in the state of Paran & aacute;. We have used employment data from the Annual Social Information Reports (RAIS) of the Ministry of Labor and Employment. The main objective of the text assumes that the collected and analyzed information have taken into account the gender of workers, schooling, age range and workers' income in the industry. An important methodological aspect concerns to the fact that we address the issue of interrelation between schooling and income from a gender perspective, using industry segmentation among the activities with higher and lower technology ratio as parameter for the analysis. This segmentation was performed by grouping of activities listed in the National Classification of Economic Activities (CNAE).
Keywords: industry; labor market; gender inequality; female work